Strategi UMKM Bertahan selama Masa Pandemi Covid-19 - Anindita Trinura Novitasari (Neolectura, 2021)
Covid-19 pandemic has inflicted tremendous impacts on multiple sectors, including Micro, Small, and Medium Enterprises (Usaha Mikro, Kecil, dan Menengah/UMKM). The government policy to impose Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar/PSBB) has greatly influenced the sustainability of UMKMs. Their products selling, among other, has transformed from conventionally direct selling to the integration of online and offline selling methods that require creativity and innovation. This qualitative research is designed to recognize strategies implemented by the UMKMs in order to survive during the pandemic. The research objects are the UMKMs whereas the instrument is library studies. The finding showed a depiction that the UMKM craftsmen used a number of selling methods such as e-Commerce, Digital Marketing, product and service quality improvements, and Customer Relationship Marketing (CRM). Those methods indicate marketing modification and creativity in the forms of products and services diversification to maintain the sustainability and continuity of their businesses.